(untitled) (Research, Society and Development, 2021)
Objective: to investigate the factors related to infant deaths due to congenital anomalies in the municipalities belonging to the 14th Regional Health Region of Paraná, in the period from 2010 to 2019. Methodology: cross-sectional study based on secondary data from the Born Information System Living, Mortality Information System and Notifiable Diseases Information System. Results: the detection of anomalies before hospital discharge proved to be a protective factor against death. The following factors were associated with death: children with low birth weight (OR= 5.7, 95%CI= 3.37-9.77, p<0.001) and children of mothers without a partner (OR= 1.8, 95%CI= 1.10-2.98, p=0.019), inadequate number of prenatal consultations (OR=1.7, 95%CI= 1.01-2.84, p=0.047), double pregnancy and more (OR= 9.3, 95%CI= 1.63-53.52, p=0.031), premature birth (OR= 4.0, 95%CI= 2.39-6.85, p<0.001) and inadequate Apgar score within the first (OR= 5.5, 95%CI= 3.28-9.32, p<0.001) and fifth minute of life (OR= 8.9, 95%CI= 4.46-17.59, p<0.001). Conclusion: several factors are associated with mortality from congenital anomalies. Therefore, the importance of preventing these factors through strengthening the process of epidemiological surveillance of anomalies, family planning, adequate prenatal care and early diagnosis to improve the quality of life and survival of children with anomalies is emphasized.